Assessment of cold exposure-induced metabolic changes in mice using untargeted metabolomics - Gong, Linqiang; Zhao, Shiyuan; Chu, Xue; Yang, Hui; Li, Yanan; Wei, Shanshan; Li, Fengfeng; Zhang, Yazhou; Li, Shuhui; Jiang, Pei (Frontiers in Molecular Biosciences, 2023)
Cold exposure can effectively regulate adipose tissue metabolism. The activation of brown adipose tissue through cold exposure has numerous positive effects on metabolic health. These effects encompass enhanced glucose uptake, improved insulin sensitivity, promoted lipolysis, and reduced levels of triglyceride and cholesterol in the bloodstream. However, certain studies have indicated that cold-induced activation of brown adipose tissue might have adverse health effects, such as an increased heart rate and elevated blood pressure. Therefore, it is crucial to thoroughly examine the impact of cold exposure on the functioning of vital organs in vivo. Previous metabolomics studies have mainly focused on analyzing one or two samples from serum, brown adipose tissue, white adipose tissue, and liver. There is a significant lack of simultaneous analysis of multiple tissues regarding the metabolic changes induced by cold exposure. Therefore, our study aims to investigate the metabolic profiles of the major tissues.